Micro-Ureteroscopy as a Treatment of Renal Pelvis Lithiasis in Young Children - Parente, Alberto; Ortiz, Ruben; Fernández-Bautista, Beatriz; Burgos, Laura; Angulo, José Maria (Frontiers in Pediatrics, 2021)
Aim: Miniaturization of endoscopic instruments has allowed to improve the efficacy of kidney stone treatment in young children. Aim of the study is to evaluate the usefulness of microureteroscopy with 4.85F sheath in the treatment of renal stones in children. M&M: We present 4 cases of microureteroscopy in 3 younger than 3 years patients with renal pelvic stones. Lithiasis was unilateral in 2 female patients and bilateral in 1 male patient. Microureteroscopy was performed using a MicroPerc set 4.85F sheath, without placing a safety guide or dilating the meatus in 3 procedures. The lithotripter system used was Ho:YAG Laser with 200-μm fiber in all cases. Results: Mean operating time was 100 ± 16 minutes. There were no intraoperative complications. In all procedures, complete pulverization of the lithiasis was achieved, except in the coraliform lithiasis in which 5 mm residual lithiasis remained in the lower calyx. All patients were discharged 24 hours after the intervention. Conclusion: Microureteroscopy can be considered a new alternative for treatment of selected cases of renal pelvic stones in infants and children.